The Influence Of Profitability, Independent Board, And Audit Committee On Sustainability Reporting: The Moderating Role Of Managerial Ownership - Linda Agustina; Rizkyana, Fitrarena Widhi; Kuat Waluyo Jati; Atta Putra Harjanto; Muhammad Ihlashul'amal; Primadhani Dyah Larasati Suyatno; Dwi Fatmasari (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2025)
This research investigates the influence of profitability, the independent board of commissioners, and the audit committee on sustainability report disclosure, with managerial ownership as a moderating variable. A quantitative approach was employed in this study. The research population comprised companies listed in the LQ45 index on the Indonesia Stock Exchange (IDX) during 2018–2021. A purposive sampling method was applied, resulting in a sample of 30 companies with 120 observational data points. The analytical techniques utilized included descriptive statistics and Moderated Regression Analysis (MRA), conducted using the EViews 12 software. The findings reveal that profitability and audit committee presence do not significantly impact the disclosure of sustainability reports, whereas the independent board of commissioners positively influences such disclosures. Furthermore, managerial ownership does not moderate the relationship between profitability, the independent board, and the audit committee with sustainability reporting. This study contributes to the literature by incorporating managerial ownership as a moderating variable in examining the determinants of sustainability report disclosure.